Motivasi Berprestasi Siswa Tidak Tuntas Kriteria Ketuntasan Minimal (KKM) Pada Mata Pelajaran Sosiologi Kelas X Sma Pancasila Sungai Kakap - Nurmalasari, Nurmalasari (Jurnal Pendidikan Sosiologi dan Humaniora, 2014)
This research was conducted with the intent and purpose to amend and improve the teaching and learning process in class X SMA Pancasila Sungai Kakap, in order to better fit with the objectives to be achieved. The problem with this research is "Achievement motivation of students does not complete the completeness criteria of teaching on sociology subjects of class X SMA Pancasila Sungai Kakap ". The sub problem is as follows: (1) how to motivate students in the areas of cognitive achievement, in class X SMA Pancasila Sungai Kakap. (2) how achievement motivation in the field of improving the status and self-esteem in a child class X SMA Pancasila Sungai Kakap. (3) how to excel in the field of motivation is affiliated with other students.This study used qualitative methods, forms of research is a case study by the research subjects were students of class X SMA Pancasila Sungai Kakap.Keywords : Achievement Motivation, Students Completed Sociology Lesson Â Completeness Criteria Of Teaching.